2012
DOI: 10.3991/ijim.v6i3.2090
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Collaborative Informal Learning Design: Study of collaborative effectiveness using Activity Theory

Abstract: Abstract-Smart Mobile Devices (SMD) are there for many years but using them as learning tools started to emerge as new research area. The trend to merge collaborative learning methodology by using mobile devices in informal context is important for implementation of Learner Centric Learning (LCL). Survey and numerous studies show that more than 95% of students in colleges are users of these smart mobile devices in developed world. Developing counties are also catching up and we can see this percentage is almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…In addition, many previous research results indicated that collaborative performance and problem solving for college graduates are inadequate. The survey results showed that college graduates still tend to take a long time to adjust to their work environment, even failing to collaborate with colleagues when solving urgent problems [13], [14]. In addition, students were often only required to have high learning outcomes, but students often fail to solve non-routine problems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many previous research results indicated that collaborative performance and problem solving for college graduates are inadequate. The survey results showed that college graduates still tend to take a long time to adjust to their work environment, even failing to collaborate with colleagues when solving urgent problems [13], [14]. In addition, students were often only required to have high learning outcomes, but students often fail to solve non-routine problems.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of learning research, this condition then forms a new research sub-field of CSCL called mobile Computer-Supported Collaborative Learning (mCSCL) (Fu & Hwang, 2018;Resta & Laferrière, 2007). An important element is the integration of the characteristics of mobile devices with collaborative learning (Baloch, Abdul Rahman, & A Ihad, 2012). Thus the mobile Computer-Supported Collaborative Learning (mCSCL) is defined as the use of mobile devices as a learning tool in the classroom and outside the classroom in a collaborative learning environment (Carapina & Boticki, 2015;Zurita & Nussbaum, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…( Baloch et al, 2012;Engestro, 2001;Engeström, 1999;Li and Bratt, 2004;Uden, 2007;Zurita and Nussbaum, 2007) …”
Section: Methodsunclassified